César Dávila Andrade: la sorprendente ambivalencia de su mirada. Narrar lo incorpóreo, la pavorosa intimidad humana y la imperecedera ternura (Legados: Centenario del natalicio de César Dávila Andrade, el Faquir, Cuenca, 1918-Caracas, 1967) - Ortega Caicedo, Alicia del Rosario (2018)
This writing is a testimony of reading, a return to the Faquir, a tribute to César Dávila Andrade in the celebration of the centenary of his birth. The author re-reads some of his stories, nonfictional prose writings, letters, novels and sketches that some of his contemporaries wrote about him or converted, years later, into a novel character. What interests me is to understand how he himself looked, he looked at others and was looked at, because it is on the writer’s gaze that this seeks to reflect.